2019
DOI: 10.1080/15623599.2019.1602583
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the application of lean construction techniques concerning safety improvement in construction projects

Abstract: Lean construction management efforts could prove to be highly rewarding for the UK construction industry. This was emphasised by the Egan Committee who stated that the concepts of lean thinking would lead the UK construction industry's quest to improve quality and efficiency. Although various countries worldwide gained large benefits by adopting Lean Construction (LC) concepts, there still seems to be limited implementation of lean in the UK construction industry, over the last two decades, even after the publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…AlSehaimi et al (2009) investigated a pilot implementation of the Last Planner System (LPS) in Saudi Arabia and concluded that numerous benefits were gained, some potential barriers reported and suggested the implementation of efficient communication systems using Information and Communication Technologies (ICT). Enshassi et al (2019) addressed 39 barriers to the implementation of LC in the Middle East (ME). Hamzeh et al (2016) highlighted the first implementation of LPS in Lebanon, where several improvements were observed, but many challenges were faced.…”
Section: Introductionmentioning
confidence: 99%
“…AlSehaimi et al (2009) investigated a pilot implementation of the Last Planner System (LPS) in Saudi Arabia and concluded that numerous benefits were gained, some potential barriers reported and suggested the implementation of efficient communication systems using Information and Communication Technologies (ICT). Enshassi et al (2019) addressed 39 barriers to the implementation of LC in the Middle East (ME). Hamzeh et al (2016) highlighted the first implementation of LPS in Lebanon, where several improvements were observed, but many challenges were faced.…”
Section: Introductionmentioning
confidence: 99%
“…Health and Safety on construction job sites has become a subject of primary concern across construction industries worldwide (Zolfagharian et al 2014;Enshassi et al 2019;Furci and Sunindijo 2020). Globally, the construction industry is perceived to have one of the poorest occupational health and safety records (Hinze and Teizer 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Resultantly, these companies prefer to maintain the status quo and never try to indulge themselves in learning/implementing new management philosophies. The role of academic institutions and construction agencies in encouraging the innovative management techniques like LC is also very meager, thereby hindering the construction companies from adopting LC (Alinaitwe, 2009;Enshassi and Mohamed, 2019).…”
Section: Group 1: Unfamiliar With Lcmentioning
confidence: 99%
“…These barriers will lead to identifying factors that can be crucial for the successful implementation of lean practice in construction. After establishing the barriers for adopting LC within all population groups, strategies to overcome these barriers are identified from the literature (Bashir et al, 2015;Shang and Sui Pheng, 2014;Ballard and kim, 2007;Enshassi et al, 2019;Warcup, 2015;Ayarkwa et al, 2011, Kawish, 2017McGrawHill, 2013;Simonsen et al, 2014;Arbulu, 2016, Sarhan, 2011Shou et al, 2016, Kanafani, 2015 . The strategies for overcoming each barrier are independently investigated and are further lined up into the respective population group.…”
Section: Strategies To Overcome Barriersmentioning
confidence: 99%